Predictors of Adherence to Treatment in Behavioral Health Therapy for Latino Immigrants: The Importance of Trust - Falgas-Bague, Irene; Wang, Ye; Banerjee, Souvik; Ali, Naomi; DiMarzio, Karissa; Palao Vidal, Diego; Alegría, Margarita (Frontiers in Psychiatry, 2019)
A complex array of barriers to care influence patients’ adherence to behavioral healthcare services. Understanding barriers to care is critical to ensure sufficient dosage of treatment. This study assessed the influence of perceived barriers on Latino migrants’ prospective adherence to treatment for co-occurring mental health and substance use disorders as part of a clinical trial. Eligible participants (18-70 years-old) were recruited from community-based settings and classified according to their intervention session attendance. Baseline assessments included socio-demographic factors, clinical characteristics (i.e., depression, anxiety, post-traumatic stress disorder, substance use), psychosocial and cultural factors (i.e., ethnic identity, health literacy, discrimination) and perceived attitudinal and structural barriers to care. Treatment involved 10-sessions of cognitive-behavioral therapy, psychoeducation, and mindfulness (Integrated Intervention for Dual problems and Early Action; IIDEA) and emphasized participant’s engagement in treatment. We used multinomial logistic regression models to examine the association between barriers to care reported at baseline, sociodemographic characteristics, psychosocial and cultural factors, clinical factors, and treatment adherence. Mistrust in previous behavioral health treatment(s) was the reported barrier significantly associated with completion of the program after adjusting for clinical, psychosocial and cultural factors, with those expressing mistrust in previous treatment(s) showing higher rates of completion compared to those who did not report this barrier. Evidence-based and culturally-tailored interventions provided by ethnically matched providers may overcome cultural mistrust and increase adherence to behavioral health care among Latino immigrants.